Bildung auf einen Blick 2017 OECD-Indikatoren - OECD, Paris (W. Bertelsmann Verlag, 2017)
The focus of the study is the performance of the education systems in the 35 OECD countries, and some non-member states such as Costa Rica and Lithuania. A system of indicators developed by the OECD allows a comparison of the level and conditions of education in the participating countries. The main aspects of the study are participation in the education system, educational expenses, operational data in the education system and which results are achieved. The educational status quo within the participating countries is visualised in more than 180 figures and tables. The current edition analyses for the first time success rates at the secondary level and admission criteria for the tertiary level. A new chapter addresses the educational policy goal of the 2030 agenda.